A 1.5km-resolution gravity field model of the Moon - Hirt, Christian; Featherstone, Will (Elsevier Science BV, 2011)
We present a high-resolution lunar gravity field model (LGM2011) that provides gravity accelerations, free-air gravity anomalies, selenoid undulations and vertical deflections over the entire Moon’s surface. LGM2011 is based on the Japanese SELENE mission that provides the low- and medium-frequency constituents of the gravity field, down to spatial scales of ~78 km. At spatial scales between ~78 km and ~1.5 km, LGM2011 uses high-frequency topographic information derived from LOLA laser altimetry to approximate the gravity field signatures of many medium- and small-size impact craters for the first time. For the topography-based gravity approximation, we use Newtonian forward-modelling under the key assumptions that the SELENE and LOLA data are consistent, the high-frequency lunar topography is uncompensated and the topographic mass density is constant. The short-scale component of LGM2011 should not be relied upon in geophysical interpretations. LGM2011 can be used as an a priori model for lunar gravity field simulation and inversion studies, evaluation of past and future lunar gravity field missions, improved topographic mapping, lunar inertial navigation, and the prediction of lunar gravity acceleration and vertical deflections at any future landing sites.